2015
DOI: 10.1002/lary.25126
|View full text |Cite
|
Sign up to set email alerts
|

Lateral pharyngeal wall collapse associated with hypoxemia in obstructive sleep apnea

Abstract: 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 36 publications
6
47
0
Order By: Relevance
“…A number of studies involving DISE have indirectly reported their findings regarding epiglottis collapse in OSA patients (Table ). In a study published by Lan et al that correlated DISE findings with BMI and objective polysomnography variables in 64 patients with OSA, the authors noted that 12.5% and 26.6% of the patients had partial and complete anteroposterior epiglottis collapse, respectively . None had partial lateral epiglottis collapse and 3.1% had complete lateral collapse.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of studies involving DISE have indirectly reported their findings regarding epiglottis collapse in OSA patients (Table ). In a study published by Lan et al that correlated DISE findings with BMI and objective polysomnography variables in 64 patients with OSA, the authors noted that 12.5% and 26.6% of the patients had partial and complete anteroposterior epiglottis collapse, respectively . None had partial lateral epiglottis collapse and 3.1% had complete lateral collapse.…”
Section: Resultsmentioning
confidence: 97%
“…Epiglottis collapse during sleep has been estimated to occur in around 12% of adult patients with OSA . Based on a previous DISE study performed at our institution, epiglottis collapse may occur more frequently than previously reported in the literature . Currently, there is a lack of good understanding about the relationship between epiglottis collapse and OSA and what the most effective way to treat it is.…”
Section: Introductionmentioning
confidence: 94%
“…Lan and colleagues studied 64 OSA patients with DISE and found that 30% exhibited complete collapse of the epiglottis. 20 Cavaliere et al found that 23% of the 66 patients studied had epiglottis involvement. 21 A similar prevalence of 24% was found in Ravesloot's study of 100 consecutive OSA patients.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, some studies have reported that up to 30% of patients have complete collapse of the epiglottis[7]. Research also indicates that epiglottic collapse is difficult to treat with conventional therapies, such as oral appliances[9] and even CPAP[10, 11].…”
Section: Introductionmentioning
confidence: 99%